Hubungan Ekspresi Emosi Orang Tua dan Kecenderungan Perilaku Disruptif pada Remaja - Tobing, Elsa Meliana L; Nawangsari, Nur Ainy Fardana (Buletin Riset Psikologi dan Kesehatan Mental, 2023)
This literature review aims to examine the relationship between parental expressed emotion and disruptive behavior tendencies in adolescents. The search for research articles was carried out using certain keywords according to PRISMA guidelines. There were 6 research articles analyzed in this literature review which were obtained through the PubMed, ScienceDirect, and Google Scholar databases, which were then analyzed for the purpose, methods, samples, and research findings. The results of this literature review are in line with previous research on parental expressed emotion and adolescent disruptive behavior, which showed a significant relationship between parental expressed emotion and disruptive behavior in adolescents. The higher the level of positive parental expressed emotion, the lower the tendency for disruptive behavior to occur in adolescents. And the higher the level of negative parental expressed emotion, the higher the tendency for disruptive behavior in adolescents.